ШТУЧНИЙ ІНТЕЛЕКТ У ВІЗУАЛІЗАЦІЯХ ТВОРІВ АМВРОСІЯ ЖДАХИ 1919 РОКУ - ШКОЛЬНА, Ольга; КОВАЛЬЧУК, Остап; САПФІРОВА, Наталія (Fine Art and Culture Studies, 2025)
The legacy of Amvrosy Zhdakha (1885, Izmail – 1927, Odesa) of the late 19th – early 20th centuries is extremely diverse. The master belonged to the cohort of universal artists of the modern era and, at the same time, from 1908–1910 he worked in the stream of proto-design, ahead of industrial and environmental designers in his bold projects for the development of interiors, furniture, ceramic stoves, and dishes, whose cohort came to European art centers approximately with the beginnings of the trends of Bauhaus functionalism, Boychukism, Constructivism, and Art Deco. Currently, the work of Amvrosy Zhdakha of the design direction is stored in the collection of the V. G. Zabolotny State Scientific Architectural and Civil Engineering Library in Kyiv. A particularly significant part of it is the author’s sketches of interior and furniture designs, screens, tiled piets, and shapes of ceramic and fine ceramic dishes from 1919. 28 of them were visualized using artificial intelligence and presented by user Anton Pronenko on December 31, 2025 on the Facebook social network in the post “Visualization of furniture by Ukrainian designer Amvrosy Zhdakha”. Considering that until recently, the artistic heritage of this extraordinary author was primarily studied by his series of book illustrations, in particular, drawings for the Gospel, Taras Shevchenko’s “Kobzar”, and covers of a number of publications by Ukrainian writers, the researchers first examined materials from the artist’s work, which he prepared for the first educational course in the national tradition, “History of Ukrainian Art”. Namely, preparatory drawings for his own series «Picturesque Ukraine» (the history of the ancient inhabitants of our country based on archaeological excavations, Ukrainian types, kleynods, ethnographic studies of Easter eggs, weapons, armor, clothing, dishes of representatives of different social strata of the population). In contrast, the creative heritage of Amvrosiy Zhdakha had not previously been studied from the point of view of developing interior design projects, furniture, dishes, but only as a draftsman (he worked for several decades as a specialist in this area in one of the Odesa banks).